Three-Dimensional Modeling for Crohn's Fistula-in-Ano: A Novel, Interactive Approach. Issue 5 (May 2018) - Lam, David; Yong, Eric; D'Souza, Basil; Woods, Rodney
Abstract : BACKGROUND: Pelvic MRI allows for clear delineation of anatomy in Crohn's fistula-in-ano, although its interpretation is often difficult for nonradiologists. OBJECTIVE: The aim was to develop a 3-dimensional model where fistula tracts and their relationship to the sphincter complex can be accurately defined, which can then be rotated in multiple axes by the surgeon. DESIGN: A 3-dimensional model was created based on MRI images. An additional 3-dimensional T2-weighted sequence was added to the existing MRI protocol to obtain high-resolution images. Segmentation of the fistula tract and volume rendering of the segmented tract were performed to create the final model. SETTINGS: This was a single-center study conducted in Victoria, Australia. PATIENTS: All of the patients who had pelvic MRI for fistulating Crohn's disease between March 2016 and March 2017 had the additional MRI sequence. INTERVENTIONS: Postprocessing of MRI images was performed by a single radiologist. RESULTS: Total acquisition time for MRI images was extended to 31 minutes compared with the standard 2-dimensional protocol lasting 25 minutes. Additional postprocessing time used to create the model was ≈15 minutes. Two clinical vignettes using this model are presented and compared with conventional 2-dimensional MRI images to highlight the use of the 3-dimensional modeling technique. LIMITATIONS: This technique involves a semiautomatic process of fistula tract segmentation that requires radiologist expertise and additional postprocessing time. CONCLUSIONS: This 3-dimensional modeling technique enables accurate identification of tracts in Crohn's fistula-in-ano and improves spatial orientation for the surgeon. The model has the potential to be an invaluable preoperative tool to guide operative decision-making, as well as enabling the assessment of response to medical or surgical therapy. Abstract : Supplemental Digital Content is available in the text.